An Analysis of Information Sources of YouTube Videos Pertaining to Tattoo Removal: Cross-sectional Study - Benjamin Gallo Marin; Ogechi Ezemma; Fabio Stefano Frech; Julio C Flores Servin; Ben S Rhee; Kathleen M Mulligan; Katie A O' Connell; Isabelle Moseley; Carlos G Wambier (JMIR Publications, 2022)
BackgroundThe American Academy of Dermatology and the Food and Drug Administration recommend consultation with a dermatologist prior to undergoing laser tattoo removal. However, non-health care professionals offer tattoo removal. Understanding the information available on the internet for patients regarding tattoo removal is important given that individuals are increasingly consulting digital sources to make decisions regarding skin care. Prior research has identified that YouTube contains misinformation on dermatologic health. ObjectiveHere, we present a cross-sectional study that determined the sources of information in YouTube videos that discuss tattoo removal and described the content presented to viewers. MethodsUsing the query "tattoo removal," we reviewed English-language YouTube videos that explicitly discussed tattoo removal. The following data were recorded: profession of the presenter, tattoo removal method discussed, whether an explicit recommendation to see a dermatologist or physician was present in the video, and number of views. ResultsWe analyzed 162 YouTube videos. We found that the majority were presented by non-health care professionals (n=125, 77%), with only 4 (3.7%) records of this subset recommending viewers to seek consultation from a dermatologist to ensure safe and adequate tattoo removal. ConclusionsBased on our findings, we recommend that dermatologists and other health care professionals provide high-quality, evidence-based information to viewers on tattoo removal and encourage dermatology societies to share via their social media platforms information about the importance of consulting a dermatologist for tattoo removal.